Search for Optimal Conditions on Nickel Recovery from Spent Catalyst Wastewater by Sulfidation Method - FUCHIDA, Shigeshi; OYAMA, Keishi; ISHII, Shun; IWAI, Hisanori; TAKAHASHI, Yuko; YOKOTA, Naoki; TOKORO, Chiharu (Resources Processing, 2024)
This study aimed to find optimal conditions for the recovery of nickel (Ni) from spent catalyst wastewater via the sulfidation method with low processing and environmental loads. Simulated Ni catalyst wastewater was used, which contained high concentrations of chloride ions and methanol. It was found that preliminary neutralization is crucial to suppress the overdose of sulfidation reagents. The gasification ratio of sulfur (S) and the recovery ratio of Ni were experimentally determined and then simulated with the numerical fitting. Results indicated that the presence of methanol expanded the range of pH and S/Ni molar ratio in which safe and complete Ni recovery can be achieved, showing the effectiveness of the sulfidation method on Ni recycling from Ni catalyst wastewater.